Branching Narrative Transformation of Receipt Parinaaz di Kafe Kroasia (A Digital Humanities Approach) - Hidayatullah, Moch Jordan; Wijaya, Lila Oktavia Sona; Wati, Ananda Belqhies Retno Shinta; Fithriyah, Mazroatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article examines the transformation of the Receipt Parinaaz di Kafe Kroasia short story by Novia Adibatus Shofah into a branching narrative within the framework of Digital Humanities. The study aims to reconstruct a linear narrative text into two alternative storylines that diverge from a single central conflict, namely the moment of Parinaaz’s arrest. This transformation is materialized through digital text production in the form of a branching script and a flyer-based digital storyboard. The research employs a qualitative approach with narrative analysis, drawing on the concept of hypertextuality by Gérard Genette and digital narrative theory by Marie-Laure Ryan. The analytical procedures include identifying the narrative elements (character, trauma, and conflict), determining the branching point, and reconstructing the text from a hypotext into two hypertexts as a form of creative digital text production. The findings reveal the emergence of two distinct narrative constructions, which are presented through a branching script and a digital storyboard. This finding demonstrates that narrative transformation constitutes a practice within Digital Humanities, particularly in adapting literary texts into branching and exploratory digital narrative forms. Furthermore, the study contributes to the development of a branching narrative, based transformation model as a strategy for adapting Indonesian literary works into digital literature.